Application of mixed methodologies to increase the productivity of an agro-industrial company - Quiroz Flores, Juan Carlos (2023)
The agroindustry is one of the sectors with the highest consolidated growth detected in recent years. In Peru, this sector is an essential part of the economy, contributing considerably to the PIB and generating many jobs per year. Therefore, companies in this sector seek to improve continuously for these reasons. However, many of these have problems such as low productivity in their processes caused by a lack of organization and order in the work areas, high downtime, unnecessary movements between activities and machine failures. Due to this, the main objective of this research is to increase the productivity of the avocado production process of the selected company through an improvement proposal using 5s, SLP, TPM and work standardization. Likewise, to validate the success of the improvement proposal, the Arena software was used, the scope of the proposal covers the arrival of the raw material from the warehouses to the packing of the finished product. The results obtained were an increase in productivity of 36.62%, an increase in the general efficiency of the equipment by 18%, an increase in yield by 13% and a reduction in unproductive times by 86%.